Adolescents with Eating Disorders: Are there Identifi able Characteristics? - Kate S Seddon; Kendall Crossen (Annals of Psychiatry and Treatment - Peertechz Publications, 2017)
Aim: Adolescents with eating disorders frequently present late for treatment or not at all. This study aimed to determine whether there were any identifying characteristics of adolescents with eating disorders that might assist health care professionals with earlier detection. A secondary aim was to determine whether there were any differences between adolescents who required inpatient treatment versus outpatient treatment only. Early identifi cation could allow treatment modifi cation aiming to avoid admission. Methods: A 4 year (October 2010-October 2014) retrospective chart review of all adolescents with an eating disorder seen at Tauranga Hospital was undertaken. Data was gathered on characteristics considered potentially associated with eating disorders. Results: A total of sixty three patients were seen. Ninety four percent of the patients were female and six percent male. Patients came from a variety of socioeconomic and ethnic groups. There was a high incidence of maternal eating disorder history (18%) and a high rate of suicidal thoughts (40%). There were no statistically signifi cant differences between inpatients and outpatients, except that inpatients had higher rates of self-harm. Conclusion: Female gender continues to be the most identifi able characteristic of adolescents with eating disorders but there are few other distinctive characteristics. Health care professionals therefore must consider the diagnosis possible in all situations rather than rely on the traditional stereotype.